Sampling-based imaging model for fast source and mask optimization in immersion lithography - Sun, Yiyu; Li, Yanqiu; Liao, Guanghui; Yuan, Miao; Wei, Pengzhi; Li, Yaning; Zou, Lulu; Liu, Lihui (Applied optics. Optical technology and biomedical optics, 2022)
Current source and mask optimization (SMO) research tends to focus on advanced inverse optimization algorithms to accelerate SMO procedures. However, innovations of forward imaging models currently attract little attention, which impacts computational efficiency more significantly. A sampling-based imaging model is established with the innovation of an inverse point spread function to reduce computational dimensions, which can provide an advanced framework for fast inverse lithography. Simulations show that the proposed SMO method with the help of the proposed model can further speed up the algorithm-accelerated SMO procedure by a factor of 3.